Lipedema: exploring pathophysiology and treatment strategies – state of the art - Fabio Kamamoto; Jaqueline Munaretto Timm Baiocchi; Bernardo Nogueira Batista; Renan Diego Américo Ribeiro; Débora Aparecida Oliveira Modena; Vitor Cervantes Gornati (Jornal Vascular Brasileiro)
Abstract Lipedema is characterized by abnormal fat deposition in areas such as the arms, hips, buttocks, and thighs, sparing the hands and feet. Symptoms include pain, bruising, edema, and subcutaneous nodules, which resist traditional interventions such as diet and exercise. Despite increasing recognition, comprehensive understanding, including pathophysiological, clinical, and therapeutic aspects, has not been fully achieved. This review aims to fill gaps in knowledge of this field, to support more informed management of lipedema. This narrative review provides a deeper understanding of lipedema treatment, addressing pathophysiology and therapeutic options. The data reveal advances in knowledge, especially regarding conservative and surgical treatments, focusing on improving quality of life. However, scientific evidence supporting the safety and efficacy of various treatments is lacking. Additional research is needed to ensure safety and to enhance efficacy of management of this complex condition.